The THE DEVELOPMENT OF FIELD TEACHING PRACTICE-1 JOBSHEET FOR ISLAMIC EDUCATION GUIDANCE AND COUNSELING PROGRAM STUDENTS UIN SU MEDAN - Putra Sinaga, M. Harwansyah (Counsenesia Indonesian Journal Of Guidance and Counseling, 2024)
The aim of this research is to develop a jobsheet of Field Teaching Practice – 1 (FTP-1) for students of BKPI FITK UIN SU Medan and to describe the usefull aspects of the jobsheet. This research used development design research with 4 Development Steps (Four D) namely define, design, develop, and disseminate. The data collection tools used in this research are assessment scales, inventories, interviews, documentation studies, and also focus group discussions. The research was conducted at BKPI FITK UIN SU Medan by involving 47 students in jobsheet trial activities based on random sampling. Data were analyzed using quantitative descriptive and qualitative descriptive. Quantitative descriptives are used to analyze survey data and jobsheet assessment results from expert validators and practitioners. Meanwhile, qualitative descriptive is used to analyze data obtained based on interviews, documentation studies, and focus group discussions. The results of this research indicate that the FTP-1 jobsheet developed is suitable for use based on the results of Aiken's V > 0.63 in the five FTP-1 program activities contained in the jobsheet. Then this jobsheet was also proven to provide benefits to students of the BKPI FITK UIN SU Medan study program, such as the implementation of FTP-1 became easy, the FTP-1 procedures became clear, the implementation of FTP-1 became practical, the results of implementing FTP-1 were satisfactory, performance during FTP-1 increased , readiness to undergo FTP-1 is helped, completion of FTP-1 tasks (reports) becomes effective and efficient. This FTP-1 job sheet should be used by the BKPI FITK UIN SU Medan study program in particular and the BK study program in general.